Comparison of trends and outcomes of infective endocarditis in patients with versus without leukemia, 2002 to 2017, from a nationwide inpatient sample. Issue 3 (4th May 2023) - Agrawal, Pratik; Khan, Muhammad Zia; Mann, Chitsimran; Munir, Muhammad Bilal; Syed, Moinuddin; Raina, Sameer; Balla, Sudarshan; Patel, Brijesh
Abstract: Patients with leukemia are at an increased risk for infective endocarditis secondary to their immunocompromised state, chemotherapy, and specific risk factors such as the presence of indwelling central venous catheters. There is a paucity of data regarding temporal trends and clinical outcomes of infective endocarditis in leukemia patients. Previous studies have shown a high rate of complications related to surgical valve procedures for treatment of infective endocarditis in patients with hematological malignancies. In this study, we aimed to analyze the contemporary trends and clinical outcomes of treatment in infective endocarditis patients with and without leukemia based on data available from the Nationwide Inpatient Sample, which is a publicly accessible, large sample-sized national dataset of hospitalized patients across the US. We present key findings on baseline characteristics, microbiological profile, outcomes, rates of valve surgical procedures, and mortality in infective endocarditis patients with and without leukemia between 2002 and 2017 in the US.